Sosialisasi Penjualan Online Produk-Produk Keloria - Sihombing, Ester Hervina; Devi, Syahrani; Astuti, Yuniar Andi; Sondang, Sondang; Pilihen, Beru; Hartati, Srie (FORDICATE, 2021)
This community service activity is carried out through asocialization process through understanding and acceptance ofindividuals for their role in a group. This activity was carried out at theUD. Keloria Sehat office Jl. M. Basir Gg. Keluarga No. 19 PangkalanMasyhur, Kec. Medan Johor, Medan. Keloria is a company thatproduces and markets halal products in order to meet consumer needsand prioritize customer satisfaction through innovation. To be able toincrease sales UD. Keloria also sells online. Implementing communityservice activities which are expected to increase knowledge in terms ofbusiness marketing through internet marketing (E-Commerce), and canmotivate UMKM to run their business professionally.